Contribution à la validation initiale de la Grille d’observation d’un message de santé (GOMS) - Denise Moreau (Communication)
The efficiency of different strategies that promote health is narrowly linked to the efficiency of the messages transmitted. Until today, few efforts have been made to create a model that is practical and easily used by practitioners in promoting efficient messages about health. Witte (1992) proposes the theoretical framework of « Persuasive Health Message » (PHM) which would serve as a guide in the development of health messages. The operationalization of PHM allowed for the elaboration of la Grille d’observation d’un message de santé (GOMS), or, a grid for the observation of health messages. This article describes the elaboration of the GOMS and presents certain aspects of its validation.